Slowing Development Facilitates Arabidopsis mgt Mutants to Accumulate Enough Magnesium for Pollen Formation and Fertility Restoration - Xu, Xiao-Feng; Qian, Xue-Xue; Wang, Kai-Qi; Yu, Ya-Hui; Guo, Yu-Yi; Zhao, Xin; Wang, Bo; Yang, Nai-Ying; Huang, Ji-Rong; Yang, Zhong-Nan (Frontiers in Plant Science, 2021)
Magnesium (Mg) is an abundant and important cation in cells. Plants rely on Mg transporters to take up Mg from the soil, and then Mg is transported to anthers and other organs. Here, we showed that MGT6+/- plants display reduced fertility, while mgt6 plants are fertile. MGT6 is expressed in the anther at the early stages. Pollen mitosis and intine formation are impaired in aborted pollen grains of MGT6+/- plants, which is similar to the defective pollen observed in mgt5 and mgt9 mutants. These results suggest that Mg deficiency leads to pollen abortion in MGT6+/- plants. Our data showed that mgt6 organs including buds develop significantly slower and mgt6 stamens accumulate a higher level of Mg, compared with wild type and MGT6+/- plants. These results indicate that slower bud development allows mgt6 to accumulate sufficient amounts of Mg in the pollen, explaining why mgt6 is fertile. Furthermore, we found that mgt6 can restore fertility of mgt5, which has been reported to be male sterile due to defects in Mg transport from the tapetum to microspores and that an additional Mg supply can restore its fertility. Interestingly, mgt5 fertility is recovered when grown under short photoperiod conditions, which is a well-known factor regulating plant fertility. Taken together, these results demonstrate that slow development is a general mechanism to restore mgts fertility, which allows other redundant MGT members to transport sufficient Mg for pollen formation.